2004
DOI: 10.1108/09526860410515936
|View full text |Cite
|
Sign up to set email alerts
|

What is the potential for the use of clinical outcome measures to be computerised? Findings from a qualitative research study

Abstract: Clinical outcome measures are used in clinical audit to monitor the quality of care provided to patients. As information technology (IT) is increasingly being integrated into the delivery of health care, computerising the use of clinical outcome measures has been proposed. However, little is known about the attitudes of health professionals towards this. Aims to understand professionals' views on adapting one clinical outcome measure--the palliative care outcome scale (POS)--for use on hand-held computers. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Ten studies examined healthcare professionals’ views on the POS 18,25,3138 and one on a computerized POS version. 39 As a family version was also developed for the POS four papers included either only informal carers 40 or patients and carers. 7,17,24…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies examined healthcare professionals’ views on the POS 18,25,3138 and one on a computerized POS version. 39 As a family version was also developed for the POS four papers included either only informal carers 40 or patients and carers. 7,17,24…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies examined healthcare professionals' views on the POS 18,25,[31][32][33][34][35][36][37][38] and one on a computerized POS version. 39 As a family version was also developed for the POS four papers included either only informal carers 40 or patients and carers. 7,17,24 Translations and country of data collection Both measures have been translated into a wide range of languages (see Table 2) but not all translations followed a formal translation process (e.g.…”
Section: Versions Of Stas and Posmentioning
confidence: 99%
See 1 more Smart Citation
“…The Palliative care Outcomes Scale (POS) was used to assess patient-reported quality of care and well-being. The POS is a 12-item self-administered questionnaire (total scores range from 0-40, with higher scores being worse); a difference of one point on each item is considered clinically meaningful [ 37 - 39 ]. The Edmonton Symptom Assessment Scale (ESAS) is a 9-item, patient-reported questionnaire of symptom intensity (pain, tiredness, nausea, depression, anxiety, drowsiness, appetite, well-being, shortness of breath) with each item rated from 0 (worst) to 10 (best).…”
Section: Methodsmentioning
confidence: 99%
“…A study by Hughes et al (2004a) found that lengthy procedures implementing audit, coupled with a lack of staff time led to a 'failing' in the use of the measure across a number of care settings. There was, however, some potential for the use of the audit measure to be incorporated into information communication technologies, such as handheld computers, to facilitatethe use of audit measures (Hughes et al 2004b).…”
Section: Journal Of Health and Social Policymentioning
confidence: 99%